Religion and Spirituality in Early Childhood Education: A Phenomenological Interpretative Analysis - Chaney, Cassandra; Baumgartner, Jennifer A. (International Journal of Pediatrics and Child Health, 2019)
Religiosity and spirituality are distinct constructs that can inform the thoughts, emotions, and behaviours of humans; however, few studies have examined the role of these constructs as a frame for early education pedagogy. Given the current void in the literature, this exploratory study will examine the extent these constructs inform early education. By using Interpretive Phenomenological Analysis (IPA) as our foundation, this qualitative, pilot study involves examining the responses of six African American females related to eight questions regarding the role of religiosity and/or spirituality in their educational pedagogy. The authors will provide recommendations regarding how early child educators can use religiosity and/or spirituality to heighten the learning experience for themselves and the children in their care.